Application of Creative Problem Solving Approach to Improving Understanding of Length Measurement Concepts at MIN 14 Nagan Raya - Wijaya, Wahid Mulli Nur; Hasanah, Uswatun; Ratna, Wahyu Dwi; Wardani, Venty Furi; Ariyanti, Vivin (MANDAILING GLOBAL EDUKASIA, 2024)
Understanding the concept of length measurement is one of the basic competencies in learning mathematics in elementary schools. However, many students still have difficulty in understanding this concept, especially in connecting it to everyday life. This study aims to analyze the application of the Creative Problem Solving (CPS) approach in improving the understanding of the concept of length measurement of grade 4 students of MIN 14 Nagan Raya. The research method used is Classroom Action Research (CAR) with two learning cycles. Data were collected through observation, learning outcome tests, and interviews to determine the development of students' understanding before and after the application of CPS. The results of the study showed that the application of the CPS approach can significantly improve students' understanding. Students become more active in thinking critically and creatively in solving problems of length measurement. In addition, this strategy encourages them to be more involved in discussions and exploration of concepts, thereby increasing their motivation and interest in learning. From the results of data analysis, there was an increase in the average value of students' understanding from the first cycle to the second cycle. Thus, the CPS approach can be used as an effective alternative learning strategy in improving the understanding of the concept of length measurement for elementary school students.